Effects of Long-Term Moderate Intensity Exercise on Cognitive Behaviors and Cholinergic Forebrain in the Aging Rat. (15th July 2019) - Téglás, Tímea; Németh, Zoltán; Koller, Ákos; Van der Zee, Eddy A.; Luiten, Paul G.M.; Nyakas, Csaba
Abstract: Physical exercise is now generally considered as a strategy to maintain cognitive abilities and to prevent age-related cognitive decline. In the present study, Wistar rats were subjected to moderate intensity treadmill exercise for 6 months prior to sacrifice at 12-, 24- and 32-month of age. This chronic physical intervention was tested on motility in the Open field (OF). Cognitive functions were measured in the Morris water maze (MWM) for spatial learning and in the Novel object recognition (NOR) tests. Since learning and memory are closely associated with cholinergic forebrain function ChAT fiber density after exercise training was assessed in hippocampus, and motor- and somatosensory cortical areas. Furthermore, quantification of ChAT-positive fiber aberrations as a neuropathological marker was also carried out in these brain areas. Our results show that in OF chronic exercise maintained horizontal locomotor activity in all age groups. Rearing activity, MWM and notably NOR performance were improved only in the 32-months old animals. Regarding cholinergic neuronal innervation, apart from a general age-related decline, exercise increased ChAT fiber density in the hippocampus CA1 area and in the motor cortex notably in the 32-months group. Massive ChAT fiber aberrations in all investigated areas which developed in senescence were clearly attenuated by exercise. The results suggest that moderate intensity chronic exercise in the rat is especially beneficial in advanced age. In conclusion, chronic exercise attenuates the age-related decline in cognitive and motor behaviors as well as age-related cholinergic fiber reduction, reduces malformations of cholinergic forebrain innervation. Highlights: Chronic exercise prevented age-related decline in horizontal locomotor activity. Chronic exercise improved spatial learning and object recognition in senescent age. Exercise increased ChAT fiber density in hippocampus and neocortex of senescent rat. Exercise attenuated ChAT positive fiber aberrations in the cholinergic forebrain.